2018
DOI: 10.1186/s13046-018-0762-y
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor and heat shock protein 27 co-regulate the malignant potential of molecular apocrine breast cancer

Abstract: BackgroundThe most striking feature of molecular apocrine breast cancer (MABC) is the expression of androgen receptor (AR). We report here the mechanism of the AR in regulating the behavior of MABC.MethodsThe MABC cell line, MDA-MB-453, and the nonMABC cell line, MCF7, were used in this study. The effect of dihydrotestosterone (DHT) and heat shock protein 27 (HSP27) on cell proliferation was quantified using the cell counter kit-8 (CCK8) and clonogenic assays in vitro and by a xenograft tumor model in vivo. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…3 ). These findings present an additional regulatory control mechanism based on PTM to the canonical substrate-chaperone relationship between AR and Hsp27 established previously [ 27 , 38 ].…”
Section: Discussionsupporting
confidence: 70%
“…3 ). These findings present an additional regulatory control mechanism based on PTM to the canonical substrate-chaperone relationship between AR and Hsp27 established previously [ 27 , 38 ].…”
Section: Discussionsupporting
confidence: 70%
“…3). These findings present an additional regulatory control mechanism based on PTM to the canonical substratechaperone relationship between AR and Hsp27 established previously (27,38). AR agonist DHT stimulates transcription of mesenchymal genes and metastasis of MCF7 cells in xenograft studies (30).…”
Section: Discussionsupporting
confidence: 63%
“…In breast cancer cells, the downregulation of ROCK2 changed the hardness of the extracellular matrix, which affects the chemosensitivity of tumor cells [44]. However, in pancreatic cancer and colon cancer, ROCK2 can promote the resistance of tumor cells to chemotherapy [45,46]. This research revealed that circCUL2 may affect the cisplatin sensitivity of GC cells by regulating miR-142-3p/ROCK2 by cotransfecting circCUL2 overexpression plasmids and miR-142-3p mimics.…”
Section: Discussionmentioning
confidence: 90%